2020
DOI: 10.1136/jmedgenet-2019-106640
|View full text |Cite
|
Sign up to set email alerts
|

Higher burden of rare frameshift indels in genes related to synaptic transmission separate familial hemiplegic migraine from common types of migraine

Abstract: BackgroundFamilial hemiplegic migraine (FHM) is a rare form of migraine with aura that often has an autosomal dominant mode of inheritance. Rare mutations in the CACNA1A, ATP1A2 and SCN1A genes can all cause FHM revealing genetic heterogeneity in the disorder. Furthermore, only a small subset of the affected individuals has a causal mutation. We set out to investigate what differentiates patients with FHM with no mutation in any known FHM gene from patients with common types of migraine in both familial and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Genetic architecture of FHM may be complex; a recent study suggested that milder FHM phenotypes in certain cases can be caused by the interaction of variants in multiple genes with moderate effect instead of a single variation in 1 gene. 31 Clinical features of patients with HM with variations in PRRT2 were undistinguishable from those of attacks in individuals with variations in CACNA1A, ATP1A2, and SCN1A. 1 Penetrance of HM in those with variations of PRRT2 was high (87.7%) and similar to rates observed in those with variations in CACNA1A (67%-89%), ATP1A2 (63%-87%), and SCN1A (100%).…”
Section: Discussionmentioning
confidence: 86%
“…Genetic architecture of FHM may be complex; a recent study suggested that milder FHM phenotypes in certain cases can be caused by the interaction of variants in multiple genes with moderate effect instead of a single variation in 1 gene. 31 Clinical features of patients with HM with variations in PRRT2 were undistinguishable from those of attacks in individuals with variations in CACNA1A, ATP1A2, and SCN1A. 1 Penetrance of HM in those with variations of PRRT2 was high (87.7%) and similar to rates observed in those with variations in CACNA1A (67%-89%), ATP1A2 (63%-87%), and SCN1A (100%).…”
Section: Discussionmentioning
confidence: 86%
“…Even though numerous exploratory studies have discovered numerous genes and pathways that may contribute to migraines, additional in-depth genomic and functional studies to better understand processes may help with better outcomes for diagnosis and treatment [ 55 , 56 ]. As a result, the genetic load may affect the severity and patterns of CSD, for instance, familial hemiplegic migraine (FHM1,2), a rare form of migraine with aura, was found to have a mutation in CACNA1A, ATP1A2, and the SCN1A gene, respectively [ 57 , 58 ]. In Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Interrogating WES data in 47 HM patients, Pelzer et al failed to identify other major HM genes, but noted that most of these cases had a milder phenotype to those with CACNA1A, ATP1A2, and SCN1A mutations [34]. By analysing WES data from various migraine cohorts, Rasmussen et al found that FHM patients had a high burden of rare frameshift indels in genes involved in synaptic function compared to either familial or sporadic migraine cases [49]. HM has been mostly viewed as an autosomal dominant disorder caused by mutations in ion channel genes, but it may also be caused by mutations in other genes, or by combinations of less penetrant variants, copy number variations, or mutations that affect regulatory regions.…”
Section: Discussionmentioning
confidence: 99%